Arms and conflict in the Middle East - Attar, Riad A. (Contributions to conflict management, peace economics and development, 2009)
This study contributes to the debate on whether defense spending encourages or hinders economic growth. The effect of politics on economic growth in developing societies is assessed, with a focus on the Middle East. The study is the first to add conflict variables to the production function defense-growth model and test them empirically across countries and regions, and provide robust empirical evidence on the differential effects of interstate and intrastate conflicts on economic growth. The study provides compelling empirical evidence and guidelines to policy decision makers on how to allocate the resources of their states and adopt policies that promote political economic development. The study urges Third World leaders to improve levels of freedom, democracy, and openness of their political systems because the results confirm that political factors are at least as important as economic factors in promoting economic growth. Furthermore, the results attest that the reallocation of resources from military to the civilian sector is the sine qua non to improve the performance of developing countries' economies.